Time to NIV and mortality in AECOPD hospital admissions: an observational study into real world insights from National COPD Audits. Issue 1 (5th August 2019) - Jayadev, Anita; Stone, Robert; Steiner, Michael C; McMillan, Viktoria; Roberts, C Michael
Abstract : Background: Randomised control trial (RCT)-derived survival figures for acute exacerbation of chronic obstructive pulmonary disease admissions managed with non-invasive ventilation (NIV) have not been replicated in UK clinical audits. Subsequent guidelines have emphasised the need for timely NIV application. Methods: Data from the 2008 and 2014 national chronic obstructive pulmonary disease audits was used to analyse the association between time to NIV and mortality Results: 1032 patients received NIV in 2008, and 1612 in 2014. Overall mortality rates reduced between the audits from 24.9% in 2008 to 16.8% in 2014 but time to NIV lengthened. In 2014, 20.9% of patients received NIV within 60 min versus 24.9% in 2008 (p=0.001). The proportion of patients receiving NIV between 3 and 24 hours increased from 31.3% in 2008 to 39% in 2014 (p=0.001). Patients admitted with hypercapnic acidotic respiratory failure who received NIV within 3 hours had lower in-patient mortality than those who received NIV between 3 and 24 hours, 15.9% versus 18.4%, but this did not reach statistical significance (p=0.425), but acidotic patients receiving NIV >24 hours after admission had significantly higher mortality (28.9%, p=0.002). A second cohort admitted with hypercapnia but normal range pH, who developed later acidosis, had higher mortality (24.6%), compared with those acidotic on admission (18% p≤0.001) and an extremely high mortality when NIV was given >24 hours after admission (42.6%). Conclusion: Survival rates for those treated with NIV has improved between the two audits but remains lower than reported in RCTs. Patients who developed acidosis after admission and received NIV later in the hospital stay have even higher mortality and deserve further study and clinical attention.